Quantification of total volume by volumetric models and tapering in Eucalyptus grandis W. Hill ex Maiden (Revista de Ciências Agroveterinárias, 2019)
This study had as objective comparing the performance of equations obtained by means of volumetric models and tapering function to obtain the total individual volume with bark of Eucalyptus grandis, in Itatinga, SP. For such, 180 trees were measured through the Smalian method. After that, six volumetric and four tapering functions were selected and tested, and to select the equations that provided the best adjustment indices, adjustment and precision coefficients were used: adjusted R², standard error of the absolute estimate, as well as percentage and graphical analysis of the residual dispersion. The best volumetric models and tapering functions were subjected to the chi-square test at a significance level of 5% to verify if there was significant difference in the estimates of the equations. The volumetric and tapering function equations presented good adjustment values, a large majority with R² adjusted higher than 0.95 while having errors lower than 13%. The equations obtained using the Meyer model and the Polynomial model of the 5th degree showed the best performances, and after the chi-square test, both obtained lower values than the table, indicating that both can be used to estimate the total volume of trees.
Keywords: R statistical analysis; forest production; measurement; equality of models